Abelmoschus esculentus subfractions attenuate Aβ and tau by regulating DPP-4 and insulin resistance signals - Chien-Ning Huang; Chau-Jong Wang; Chih-Li Lin; Hsin-Hua Li; An-Ting Yen; Chiung-Huei Peng (BMC, 2020)
Abstract Background Insulin resistance could be associated with the development of Alzheimer disease (AD). The neuropathological hallmarks of AD are beta amyloid (Aβ) produced from sequential cleavage initiated by β-secretase and degraded by insulin degradation enzyme (IDE), as well as hyperphosphorylation of tau (p-tau). Insulin action involves the cascades of insulin receptor substrates (IRS) and phosphatidylinositol 3-kinase (PI3K), while phosphorylation of IRS-1 at ser307 (p-ser307IRS-1) hinders the response. Our previous report suggested dipeptidyl peptidase-4 (DPP-4) is crucial to insulin resistance, and the subfractions of Abelmoschus esculentus (AE), F1 and F2, attenuate the signaling. Here we aim to investigate whether AE works to reduce Aβ generation via regulating DPP4 and insulin resistance. Methods The subfractions F1 and F2 were prepared according to a succession of procedures. F1 was composed by quercetin glycosides and triterpene ester, and F2 contained a large amount of polysaccharides. The in vitro insulin resistance model was established by SK-N-MC cell line treated with palmitate. MTT was used to define the dose range, and thereby Western blot, ELISA, and the activity assay were used to detect the putative markers. One-way ANOVA was performed for the statistical analysis. Results Treatment of palmitate induced the level of p-ser307IRS-1. Both F1 and F2 effectively decrease p-ser307IRS-1, and recover the expression of p-PI3K. However, the expression of total IRS plunged with 25 μg/mL of F1, while descended steadily with 5 μg/mL of F2. As palmitate increased the levels of Aβ40 and Aβ42, both AE subfractions were effective to reduce Aβ generation of and β-secretase activity, but IDE was not altered in any treatment conditions. The expression of DPP4 was also accompanied with insulin resistance signals. Inhibition of DPP4 attenuated the activity of β-secretase and production of Aβ. Moreover, the present data revealed that both AE subfractions significantly decrease the level of p-Tau. Conclusions In conclusion, we demonstrated that AE would be a potential adjuvant to prevent insulin resistance and the associated pathogenesis of AD, and F2 seems more feasible to be developed.